E-Commerce and Digital Economy: An Analysis of Changing Consumption Patterns and Their Impact on Economic Growth - Adisti Maharani Krisna (Oikonomia : Journal of Management Economics and Accounting, 2025)
This research aims to comprehensively examine the influence of e-commerce development on Indonesia's economic growth through a literature study method that explores various relevant and up-to-date primary and secondary sources. This study aims to comprehensively examine the influence of e-commerce development on Indonesia's economic growth through a literature study method that explores various primary and secondary sources that are relevant and up-to-date. The development of information and communication technology (ICT) and increased internet penetration are fundamental factors driving the acceleration of digitization and overall economic growth. A number of significant obstacles remain a major challenge, such as the digital divide that still exists between urban and rural areas, the low level of digital literacy of the community, regulations that are not fully adaptive to the dynamics of technological development and digital business. Optimizing the potential of e-commerce in a sustainable manner and making a significant contribution to national economic growth, as well as encouraging equitable distribution of public welfare in the era of the digital economy. The results show that increased digital consumption and e-commerce transactions have a positive relationship with economic growth. This change in consumption patterns not only increases the efficiency of the distribution of goods and services, but also encourages the growth of the information technology sector, the creative economy, and the creation of new jobsThis research contributes to the development of an inclusive and sustainable digital economy strategy.